Advances in the Study of Lens Refilling - Wen-Wen Zhang; Zheng-Gao Xie (Journal of Ophthalmology)
The ultimate goal of cataract surgery is to restore the accommodation while restoring distance visual acuity. Different kinds of accommodative intraocular lens (IOLs) and surgical techniques have been suggested to apply during the surgery, but they showed poor postoperative accommodation. It is possible to achieve this goal by refilling the lens with an injectable polymer. We present a summary of the existing materials, methods, results, and some obstacles in clinical application that remain of lens refilling for restoration of accommodation. Two main problems have restricted the clinical application of this technique. One was the formation of postoperative secondary capsule opacification and the other was the different accommodative power after surgery.